Oxidation corrosion resistant die steel and preparation method thereof

By optimizing the composition and process of mold steel, intermetallic compounds are formed to replace carbides, which solves the problem of insufficient performance of mold steel in high-temperature oxidation, corrosive gas erosion and high-temperature and high-pressure environments, and improves wear resistance and corrosion resistance, making it suitable for the manufacture of large-size molds or parts.

CN121472723APending Publication Date: 2026-02-06JIANGSU POLYTECHNIC COLLEGE OF AGRI & FORESTRY +1

Patent Information

Application Number
CN202511585687.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing mold steel materials cannot simultaneously meet the requirements of high hardness and corrosion resistance, large size and uniformity, as well as high-efficiency production and environmental protection. In particular, their performance is insufficient in high-temperature oxidation, corrosive gas erosion, and high-temperature and high-pressure environments, and traditional processes have pollution problems.

Method used

By optimizing the composition design and adding specific proportions of elements such as C, Si, Mn, Cr, Mo, W, Al, Ni, Cu, Mg, Zn, Ca, B, and La+Ce, combined with vacuum induction melting, electrode ingot casting, electroslag remelting, rolling, and heat treatment processes, intermetallic compounds are formed to replace some carbides, improving the wear resistance and oxidation corrosion resistance of the material. Furthermore, high-temperature diffusion and forging processes promote the homogenization of the microstructure.

Benefits of technology

We have obtained mold steel materials with resistance to oxidation and corrosion, excellent surface properties, and balanced comprehensive mechanical properties. These materials are suitable for manufacturing large-size molds or parts, improving the wear resistance, corrosion resistance, and high-temperature performance of the materials, while reducing production costs and environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses oxidation corrosion resistant die steel which comprises the following components in percentage by weight: 0.36-0.47% of C, 0.81-0.89% of Si, 0.83-1.21% of Mn, 19.41-22.51% of Cr, 4.75-5.25% of Al, 0.50-0.75% of Ni, Mo, W, Cu, Mg, Zn, Ca, B, rare earth elements La and Ce, and the balance of Fe and impurities, and Zn / (Mg + La + Ce) is more than or equal to 0.75 and less than or equal to 2.50, and B / (Zn + Ca) is more than or equal to 0.09 and less than or equal to 0.31. The die steel has excellent oxidation corrosion resistance and good comprehensive mechanical properties and surface properties, and is suitable for manufacturing large-size dies or parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to mold steel and its preparation method, specifically to an oxidation- and corrosion-resistant mold steel and its preparation method. Background Technology

[0002] Resin, plastics, rubber, and glass products are widely used in the national economy, and the quality of mold materials directly determines the added value and production cost of products. Currently, mold materials face multiple challenges: substandard surface roughness prevents the production of high-value-added products (such as vehicle glass and resin lenses); uneven hardness easily leads to localized wear and failure, resulting in overall scrap; materials such as ABS and PVC release corrosive gases during hot melting, shortening mold life; and companies prefer one-piece molding processes, requiring larger mold material dimensions, but existing materials struggle to balance performance and cost.

[0003] In traditional material systems, martensitic stainless steels with a chromium content of 12-19 wt% (such as the Cr17 and Cr12 series) were once the mainstream choice, possessing basic corrosion resistance, but suffering from defects such as poor mirror polishing performance and high risk of stress cracking. Although relevant standards (GB1299, YB191, ASTM D2, etc.) have been referenced, the overall performance of the materials is still insufficient to meet the requirements of complex working conditions.

[0004] Patent application number 202111316559.1 improves material uniformity by optimizing rolling and continuous casting processes; patent application number 202110172244.8 proposes pickling and shot blasting to improve surface quality, but this involves contamination issues. Patent application number 201210406748.2 enhances strength and corrosion resistance by adding elements such as nickel, cobalt, and molybdenum, but this can easily lead to decreased formability or increased process complexity. Patent application number 201510872111.6 achieves the preparation of materials with diameters of 450mm and 710mm, respectively, but is mostly limited to cold forming scenarios. Existing technologies struggle to simultaneously meet the requirements of high hardness and corrosion resistance, large size and uniformity, and efficient production and environmental protection.

[0005] As products become more multi-cavity, integrated, and precision-oriented, mold materials face increasingly stringent requirements. Rubber injection molding requires high-temperature oxidation resistance during vulcanization; corrosive gases erode the mold during PVC molding; metal powder undergoes high temperature and pressure during thermoforming; and carbon fiber autoclaves experience stress concentration due to alternating hot and cold temperatures. Even localized damage can lead to significant economic losses, necessitating the development of material systems with superior overall performance.

[0006] The role of nitrogen in metallurgy is controversial. Patent application number 201810433208.7 considers it beneficial, while application number 202110755633.3 considers it harmful. Patent application number 202111103042.4 proposes a balanced ratio of elements such as molybdenum and cobalt, which, while improving strength, may worsen weldability. Insufficient synergy between composition adjustments and process parameters (such as heat treatment and continuous casting) leads to large fluctuations in material properties. Existing patented technologies have comprehensively optimized metallurgy, forming, and surface treatment, but the core contradictions remain unresolved: high-alloy materials result in soaring costs, while low-alloy materials suffer from insufficient performance; multiple processes lead to a decrease in yield; and processes such as pickling pose environmental risks. Summary of the Invention

[0007] Objectives of this invention: The objective of this invention is to provide a mold steel material that is resistant to oxidation and corrosion, has excellent surface properties, balanced comprehensive mechanical properties, and is suitable for manufacturing large-size molds or parts; another objective of this invention is to provide a method for preparing an oxidation-resistant mold steel; this invention also provides a nitrogen-containing wear-resistant and oxidation-resistant mold steel with good mirror finish and wear resistance; this invention further provides a method for preparing a nitrogen-containing wear-resistant and oxidation-resistant mold steel.

[0008] Technical Solution: The present invention discloses an oxidation- and corrosion-resistant mold steel, comprising the following components by weight percentage: C: 0.36~0.47%, Si: 0.81~0.89%, Mn: 0.83~1.21%, Cr: 19.41~22.51%, Mo: 0.07~0.10%, W: 0.02~0.03%, Al: 4.75~5.25%, Ni: 0.50~0.75%, Cu: 0.01~0.02%. %, Mg: 0.01~0.02%, Zn: 0.03~0.05%, Ca: 0.002~0.005%, B: 0.005~0.010%, La+Ce: 0.01~0.02%, S≤0.011%, P≤0.020%, with the balance being Fe and unavoidable trace impurities, and simultaneously satisfying 0.75≤Zn / (Mg+La+Ce)≤2.50, 0.09≤B / (Zn+Ca)≤0.31.

[0009] Furthermore, the total content of O and N in trace impurities: O+P≤12 ppm.

[0010] Furthermore, the mass percentage of P is P≤0.005wt%.

[0011] C: Carbon is an essential element in steel. It enters the matrix through interstitial solid solutions, increasing the matrix's hardness and strength, and mitigating ferrite softening caused by high chromium and aluminum content. Carbides improve the material's toughness and wear resistance. The combined addition of carbide-forming elements such as chromium and tungsten, as well as boron, can reduce the formation of single carbides, slow their growth, and prevent the merging and coarsening of different carbides. Furthermore, the adjustment of carbon diffusion by elements such as silicon promotes the formation of fine, dispersed carbides, hindering dislocation activation and slip, and improving the material's thermal strength. Excessive carbon content is detrimental to the material's weldability, making large molds or parts difficult to repair. An optimal carbon content of 0.36–0.47 wt% is preferred, maintaining the material's weldability while achieving good wear resistance and hardness.

[0012] Silicon (Si): Silicon is a ferrite-forming element, which helps improve the dimensional stability of materials under varying environmental temperatures, facilitating the fabrication and application of high-precision molds or parts. Furthermore, silicon slows down the diffusion rate of carbon in the matrix, reducing the aggregation of carbides at high temperatures, thereby increasing tempering stability and preventing softening during tempering, while also improving the stability of materials under long-term alternating hot and cold conditions. Silicon can enter ε-carbides through substitutional solid solution, promoting coherence between the carbides and the matrix lattice, thus improving the material's strength and toughness. Silicon also improves hardenability and enhances the material's oxidation resistance by forming a passivation layer, or enhances corrosion resistance by influencing pitting potential, reducing the material's tungsten and molybdenum requirements. However, excessive silicon content is detrimental to the material's isotropic properties; a silicon content of 0.81–0.89 wt% is preferred, as it improves the material's resistance to softening while achieving excellent oxidation and corrosion resistance and stability.

[0013] Mn: Manganese plays a multifaceted role in this invention. Manganese significantly improves hardenability, thereby promoting a more uniform increase in the microstructure and hardness of large-sized materials. Manganese, entering the matrix through substitutional solid solution, can improve the strength and hardness of the material without affecting its ductility. Manganese can not only dissolve into the matrix but also into carbides, improving their high-temperature stability and promoting a more dispersed distribution, thus enhancing the material's toughness. For large molds or parts, repairing partially failed areas is an important way to extend equipment life and reduce costs. Taking welding repair as an example, in this invention, the addition of manganese helps to obtain a fine and uniformly distributed acicular ferrite microstructure at the weld. During the cooling process after weld heating, the transformation of acicular ferrite is a coherent shear, which can increase dislocation density and improve the strength and toughness of the weld. Furthermore, manganese is an important sulfide-forming element; by being added in combination with elements such as calcium, it can promote the transformation of sulfides to a spindle-shaped or quasi-spherical shape, improving the isotropic mechanical properties of the material. However, excessive manganese content is detrimental to the machinability of the material. It is preferable to use 0.83 to 1.21 wt% manganese, which can improve the welding performance of the material while obtaining excellent hardness and uniformity.

[0014] Cr: Chromium's improvement on hardenability is lower than that of manganese, but its content exceeds that of manganese. Therefore, its contribution to improving the uniformity of material microstructure by enhancing hardenability is significant. As the alloying element with the highest content in this invention, chromium has a significant impact on the effects of other elements. For example, in high-temperature oxidizing environments, chromium can form an oxide layer that covers a silicon-rich oxide layer, working together to improve the material's resistance to high-temperature oxidation. Furthermore, chromium is an important carbide-forming element. During tempering, it forms MC-type carbides with high hardness and thermal stability, inhibiting carbide aggregation and growth at high temperatures, and improving the material's high-temperature strength by pinning dislocations. The addition of chromium increases the material's self-corrosion potential and significantly reduces the corrosion current density, thereby giving the material good resistance to uniform corrosion. Together with silicon and molybdenum elements that improve pitting corrosion resistance, it provides comprehensive corrosion resistance to the material. However, excessive chromium content tends to accumulate and segregate in the core. This invention preferably uses 19.41~22.51 wt% chromium to improve the material's microstructure uniformity while achieving good resistance to oxidation and corrosion.

[0015] Mo: Molybdenum can exist in steel materials in various forms, and its role in this invention is multifaceted. Molybdenum can combine with carbon to form various carbides, including MC and MC2 type carbides with high hardness and stability. This improves material strength through dispersion strengthening while avoiding the formation of single coarse carbides. Molybdenum can also be tempered at high temperatures to form M6C, improving the material's resistance to softening through secondary hardening. Molybdenum can combine with nitrogen to fix it. In addition to non-metallic elements, molybdenum can also form intermetallic compounds such as Ni3(Mo / Al) and Fe2Mo, further enhancing precipitation strengthening effects. Molybdenum can also function independently, entering steel in solid solution to form Cochrane gas clusters, which agglomerate around dislocations, hindering dislocation activation while reducing the degree of lattice distortion in the matrix and improving material strength. Furthermore, molybdenum has good corrosion resistance to acidic media, especially crevice corrosion. It can fill crevices by forming molybdates, reducing the contact between the matrix and corrosive media and improving the material's corrosion resistance. However, excessive molybdenum content can affect the toughness of the material. Therefore, this invention preferably uses 0.07 to 0.10 wt% molybdenum to improve the hardness and strength of the material while obtaining excellent corrosion resistance.

[0016] Tungsten, as a medium-sized carbide-forming element, can form highly stable M6C, which can hinder the coarsening of single carbides and improve the hot strength of materials. Furthermore, tungsten can form MC and M2C type carbides, which can act as nucleation sites during solidification to increase grain size, or enhance fine-grain strengthening by inhibiting grain growth and improving the red hardness of materials. The tungsten-containing carbides precipitated during tempering are small in size and diffusely distributed, providing secondary hardening or resistance to tempering softening. Moreover, tungsten can form Fe2W or Fe2(Mo / W), increasing material strength through precipitation strengthening. When materials come into contact with corrosive media, especially those containing chloride ions, tungsten can combine with iron to form substances such as Fe2(WO4)3. These insoluble tungsten oxides cover the substrate surface, supplementing the chromium oxide layer and inhibiting the spread of localized corrosion. Tungsten also improves the high-temperature creep strength of weld metal, thereby enhancing the usability of materials after weld repair. However, tungsten is too expensive. Therefore, this invention prefers 0.02 to 0.03 wt% tungsten, which improves the red hardness of the material while obtaining good strength and corrosion resistance.

[0017] Aluminum plays a multifaceted role in this invention. During smelting, it deoxidizes and fixes nitrogen, forming inclusions of types B and C, which are then removed by electroslag remelting, thereby improving the material's mirror polishing performance. During solidification and heat treatment, aluminum, as a ferrite-forming element, weakens the chemical bonds between iron atoms, transforming them into iron-aluminum or nickel-aluminum bonds. The resulting intermetallic compounds can improve matrix purity while, due to their higher thermal conductivity compared to carbides, reducing heat accumulation during machining and improving machinability. Dispersed aluminum-containing intermetallic compounds can increase the material's yield strength and high-temperature strength, partially replacing more expensive elements such as tungsten and cobalt, and have less impact on mirror polishing performance than carbonitrides. Furthermore, the combined addition of aluminum and zinc can increase the supercooling of the molten steel, refine the grain structure of the cast-state microstructure, and improve the potential grain coarsening trend in materials containing more ferrite-forming elements such as chromium. In addition, the addition of aluminum can also improve the yield by enhancing the material's hot working properties. During service, aluminum can increase the material's absorption of stress, reduce crack initiation, and form a passivation film to improve the material's resistance to oxidation and corrosion. However, excessive aluminum content increases the difficulty of smelting. This invention preferably uses 4.75~5.25wt% aluminum, which improves the material's resistance to high-temperature oxidation and corrosion while also achieving good machinability and mirror polishing performance.

[0018] Ni (Ni): Nickel can enter the matrix through solid solution, improving the hardenability and strength of the material. At high temperatures, nickel can hinder the diffusion of carbon and slow down the rate at which carbides integrate into the matrix, thereby inhibiting grain growth and expanding the heat treatment temperature range of the material, laying the foundation for improving high-temperature diffusion and quenching temperature. Similarly, during tempering, nickel can also improve the high-temperature hardness of the material by inhibiting carbide growth. Nickel can also act in conjunction with other elements; it can form a composite chromium-nickel spinel oxide with chromium, which has better resistance to oxidation and corrosion than single oxides. Nickel can also form intermetallic compounds with aluminum, which can inhibit HAZ softening. Nickel can also inhibit copper precipitation and prevent copper cracking. However, nickel is expensive and should not be added in large quantities. This invention preferably uses 0.50~0.75wt% nickel to achieve good high-temperature hardness while improving the material's resistance to oxidation and corrosion.

[0019] Copper (Cu) plays a crucial role in strengthening the matrix. It can enter the matrix through displacement solid solution to enhance its strength. Due to the limited solubility of copper in ferrite and the electronegativity difference between copper and iron, copper-iron alloys readily form ordered microstructures with blurred boundaries with the matrix, hindering dislocation activation. At some boundary locations with higher copper content, these ordered microstructures form nanoparticles during cooling, improving material toughness through precipitation strengthening. Furthermore, the combined addition of manganese and copper provides additional nucleation sites for copper precipitation, promoting the dispersed precipitation of the precipitate phase. Some copper combines with nickel, acting as a secondary hardening agent in the form of metallic compounds, further enhancing material strength. Moreover, copper can activate the anode, promote cathode passivation, and combine with sulfide ions to form acid-insoluble cuprous sulfide, improving corrosion resistance. However, excessively high copper content can lead to copper cracking. This invention preferably uses 0.01~0.02 wt% copper to achieve good strength and toughness while improving corrosion resistance.

[0020] Mg: Magnesium can refine carbides by adjusting the interfacial energy of materials. As a surface-active element, magnesium tends to exist at the interface and participate in the formation of complex carbides, increasing the surface free energy of carbides and thus promoting carbide fragmentation and refinement, reducing the number of large-sized carbides. This plays an important role in improving mirror properties and toughness. Magnesium has a strong affinity for oxygen and can form spinel inclusions with aluminum, promoting the transformation of hard and clustered alumina inclusions into fine and dispersed complex inclusions. It can serve as a nucleation site to refine grains and improve material toughness. Magnesium also has a modifying effect on sulfide inclusions, transforming them from thin-film or chain-like type II inclusions to spherical type I inclusions. In addition, magnesium can also work with calcium to blunt the sharp corners of type III inclusions and reduce their coarseness by 0.5 grade, improving the overall mechanical properties of the material. Furthermore, magnesium has a fixing effect on phosphorus, forming magnesium-phosphorus composite oxide inclusions, reducing the occurrence of cold brittleness. Finally, the addition of magnesium promotes the transformation of cutting chips into short C-shapes, improving the material's machinability. However, magnesium's effect on adjusting carbide morphology is parabolic, meaning that excessive amounts will reduce its effectiveness. This invention preferably uses 0.01~0.02wt% magnesium to achieve good toughness while improving the material's mirror polishing performance.

[0021] Zinc (Zn) can improve the oxidation and corrosion resistance of materials. Firstly, zinc increases the bonding force between the oxide layer or passivation film and the substrate, reducing the cracking and peeling of oxides in alternating hot and cold environments, thus improving the material's oxidation and corrosion resistance and stability. Secondly, the addition of zinc can increase the diffusion rate of chromium, promoting chromium diffusion to the surface and forming oxides to protect the substrate. This promotion of chromium diffusion can also reduce segregation; combined with high-temperature diffusion treatment, it also improves the segregation of elements such as manganese and silicon, enhancing the uniformity of large-sized materials. Zinc can also combine with magnesium to form intermetallic compounds, replacing some carbides near grain boundaries to hinder growth, refining grains and improving material strength. Furthermore, the reduction of carbides is beneficial for improving the material's mirror polishing performance. Zinc, magnesium, and rare earth elements can all improve the morphology of carbides and inclusions. By adjusting the ratio (0.75≤Zn / (Mg+La+Ce)≤2.50), significant effects can be achieved while reducing costs. At this point, zinc can promote the growth and flotation of inclusions during smelting, while magnesium, lanthanum, and other elements modify the inclusions to prevent large, sharp inclusions from remaining in the steel and causing defects such as cracking. However, excessive zinc can affect the high-temperature impact resistance of the material. This invention preferably uses 0.03~0.05wt% zinc to improve the material's resistance to oxidation and corrosion while achieving good uniformity.

[0022] Ca (Calcium): Calcium plays a role in modifying inclusions. The addition of calcium promotes the transformation of alumina into inclusions such as aluminum calcate, which have relatively low hardness, improving the material's machinability and polishing performance. Calcium can also promote the transformation of sulfur-containing inclusions into a spindle shape, improving the material's isotropic properties. Calcium, in conjunction with rare earth elements, facilitates the coalescence of inclusions during the smelting stage, promoting their flotation and removal to purify the molten steel. Calcium also adjusts the type and quantity of carbides, lowering the decomposition temperature of liquid-precipitated carbides and promoting their decomposition during high-temperature diffusion treatment and quenching, thereby reducing the probability of stress concentration and cracking caused by excessively large carbide sizes. Calcium has extremely strong deoxidizing capabilities, enabling deep forced deoxidation during electroslag remelting, preventing intergranular cracking in electroslag ingots due to insufficient aluminum deoxidation, thus laying the foundation for the preparation of large-size materials. Calcium also has a dearsenic removal effect, but adding large amounts of calcium does not significantly improve the effect. A preferred concentration of 0.002~0.005 wt% calcium improves the material's mirror polishing performance while achieving good isotropic properties.

[0023] B: Boron's smaller atomic radius makes it prone to entering defects at grain boundaries, reducing total free energy, increasing matrix stability, and improving hardenability. Compared with other elements, boron is more beneficial for weldability. In the technical solution of this invention, boron can form M2B-type borides, replacing some carbides to pin grain boundaries and hinder dislocation slip, thereby improving material strength. Furthermore, the formation of borides can hinder the growth and connection of carbides, avoiding the formation of network carbides. Borides themselves have higher thermal stability and a smaller growth tendency, which can increase the service temperature of the material. Some boron can enter intermetallic compounds, improving their high-temperature strength and resistance to softening. Boron, along with zinc and calcium, has the effect of purifying grain boundaries and improving hardenability, but the mechanisms of action are different. Boron needs to be in its elemental state to exert its relevant effects most effectively. Therefore, its ratio with zinc and calcium needs to be controlled, 0.09≤B / (Zn+Ca)≤0.31, to promote the combination of zinc and calcium with impurity elements at the interface while retaining boron in its elemental state. However, excessive boron can easily capture hydrogen, causing grain boundary cracking. The present invention preferably uses 0.005~0.010 wt% boron, which improves hardenability while obtaining good resistance to softening.

[0024] La+Ce: Lanthanum and cerium both belong to the rare earth elements, and their atomic numbers differ by one, which determines their similarity in physical properties and functions. Lanthanum and cerium have the effect of purifying grain boundaries, promoting the transformation of elongated sulfide inclusions into spindle-shaped or spherical inclusions, improving the isotropy of the material and increasing its ductility and toughness. For oxides, lanthanum, cerium, and magnesium work together to promote the transformation of high-hardness alumina inclusions into magnesium-containing sulfur-oxygen complex inclusions, promoting their flotation during smelting and reducing their quantity and hardness after solidification. The resulting modified fine oxides or sulfides can act as nucleation sites, promoting microstructure refinement, inhibiting the coarsening of borides or carbides, improving material toughness, and enhancing its weldability, which is beneficial for the preparation of large-sized parts or molds. Lanthanum and cerium, in combination with chromium and aluminum, improve the adhesion of the oxide layer, reduce the cracking and peeling of the oxide layer, and thus improve the oxidation and corrosion resistance of the material. Excessive lanthanum and cerium will increase manufacturing costs. It is preferable to use a total lanthanum and cerium content of 0.01 to 0.02 wt% to improve the toughness of the material while obtaining good isotropy and ductility.

[0025] Sulfur and phosphorus (S and P) content in steel should be as low as possible. During the smelting stage, vacuum induction melting followed by electroslag remelting is used, with magnesium, calcium, zinc, and rare earth elements added to remove sulfur. Residual sulfur in the steel is modified with alloying elements such as manganese and magnesium, promoting its transformation into spindle-shaped or spherical forms, thus improving the material's machinability while reducing its harmful effects. For residual phosphorus, grain boundaries are purified using rare earth elements, and molybdenum is added to bind with it, preventing its segregation at grain boundaries and thus preventing brittle fracture. Residual phosphorus dissolved in ferrite increases matrix hardness and improves mirror polishing performance. The preferred sulfur and phosphorus content is S ≤ 0.011 wt% and P ≤ 0.020 wt%. Furthermore, when the content of magnesium, zinc, and calcium is at its upper limit, the phosphorus content is preferably ≤ 0.005 wt%, avoiding brittle fracture while improving strength and achieving good mirror polishing performance.

[0026] O and N: Oxygen and nitrogen are harmful impurity elements in this invention and should be minimized. High vacuum and argon protection are used during the smelting stage to remove oxygen and nitrogen, preventing them from affecting mirror polishing performance. For the portions that cannot be removed, calcium, magnesium, and rare earth elements are added to adjust their morphology, preventing the formation of large inclusions and promoting the transformation of oxide inclusions into spherical or spindle shapes, thus improving the material's isotropy. Alternatively, boron is used to replace these inclusions or to partially replace elements in oxides or nitrides through substitutional solid solution, reducing their hardness. Preferably, the total oxygen and nitrogen content in this invention is ≤12 ppm, maintaining the mirror polishing performance of the matrix while adjusting the number, properties, or excellent isotropy of inclusions.

[0027] The present invention discloses a method for preparing an oxidation- and corrosion-resistant mold steel, comprising the following steps.

[0028] (1) Vacuum induction melting: The raw materials are sequentially filled into the vacuum induction melting process. The vacuum degree is less than 1 Pa for a period of not less than 10 min. The melting is carried out under argon protection to obtain molten steel.

[0029] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 280~300℃. After casting, it is slowly cooled to room temperature at a rate of 25~35℃ / h to obtain an electrode ingot.

[0030] (3) Electroslag remelting: After removing impurities from the electrode ingot obtained in step (2), it is placed in an ESR furnace and electroslag remelted using a TiO2-Ce2O3-Al2O3 slag system under argon protection. The ingot is then cooled to obtain a steel ingot.

[0031] (4) Rolling or forging: The steel ingot obtained in step (3) is rolled or forged.

[0032] (5) Heat treatment: Quenching and tempering the steel ingot obtained in step (4) at a quenching temperature of 1060~1110℃, cooling to room temperature and then immediately tempering at a tempering temperature of 610~645℃ to obtain oxidation and corrosion resistant mold steel.

[0033] Furthermore, the oxidation-resistant mold steel obtained in step (5) is subjected to surface processing, and after fine grinding and polishing, a high mirror-finish oxidation-resistant mold steel with a surface roughness of less than 0.020 μm is obtained.

[0034] Furthermore, in step (1), the order of filling materials is as follows: tungsten, molybdenum, nickel, manganese, chromium, copper, and iron are melted, then 1 / 2 to 2 / 3 of aluminum and silicon are added; calcium, magnesium, and carbon are added under a vacuum of less than 1 Pa; and finally, the remaining raw materials are added. This sequential addition promotes alloying and avoids significant loss of volatile elements.

[0035] Furthermore, in step (4), before forging, a high-temperature diffusion treatment of 1200~1260℃ is performed, with an initial forging temperature of 1135~1190℃ and a final forging temperature of 955~980℃, and a total forging ratio of 7~9. An upsetting and drawing method is adopted. During upsetting, a small reduction of 20% is used for uniform upsetting first, followed by a larger reduction. During drawing, cross-forging is used. The high-temperature diffusion treatment can promote the homogenization of composition, reduce core segregation, and improve the potential coarsening defects in the microstructure caused by high chromium and aluminum content at high temperatures.

[0036] Furthermore, the quenching holding time in step (5) is 1.1~1.6 min / mm, and the tempering holding time is 2.5~3 min / mm, to avoid coarsening of the structure at high temperature. Secondary tempering can promote secondary hardening and improve wear resistance.

[0037] Further, the quenching temperature conditions in step (5) are as follows: the first stage heating rate is 60~65℃ / h to 560~580℃ and held for 1.5~2 h; the second stage heating rate is 80~85℃ / h to 850~870℃ and held for 1.5~2 h; and finally heating rate is 95~100℃ / h to the quenching temperature.

[0038] Furthermore, in step (5), the cooling adopts a combination of atomization cooling and air cooling, with an air-to-water pressure ratio of 5:2.5~3.5 and an atomization nozzle pressure of 0.35~0.55 MPa.

[0039] The principle behind the oxidation and corrosion resistant mold steel and its preparation method is as follows: Through the complementary strengthening effects of the components, intermetallic compounds are used to replace some carbides to improve mirror polishing performance. Higher chromium and aluminum content is used to achieve oxidation and corrosion resistance, while small amounts of tungsten, molybdenum, and nickel are used to improve high-temperature performance. Magnesium, calcium, and rare earth elements are used to modify inclusions. Combined with high-temperature diffusion and forging processes, the microstructure is homogenized, ultimately resulting in a mold steel material suitable for manufacturing large-sized molds or parts. It is applicable in high-precision forming of plastics, glass, or rubber, aluminum-titanium alloy injection molding, and in applications involving contact with oxidizing and corrosive media.

[0040] This invention also includes a nitrogen-containing wear-resistant and oxidation-resistant mold steel, comprising the following components by weight percentage: C: 0.32~0.45%, Si: 0.47~0.65%, Mn: 2.65~5.25%, Cr: 17.20~19.20%, V: 0.23~0.47%, Co: 0.15~0.29%, Ni: 0.75~1.05%, Al: 0.14~0.23%. %, Ti: 0.05~0.10%, N: 0.05~0.18%, Mg: 0.002~0.007%, Zr+Nb: 0.01~0.03%, Ce: 0.005~0.010%, S≤0.015%, P≤0.015%, with the balance being Fe and unavoidable impurities, and simultaneously satisfying 0.44<(Ti+V+Zr+Nb) / (Si+Mg)≤1.27.

[0041] C: The mechanism by which carbon plays a role in this invention is multifaceted. In the smelting stage, carbon has a deoxidizing effect; in the solidification stage, carbon can form carbides, acting as nucleation sites to promote grain refinement; in the forging stage, multi-directional forging is required to break down coarse carbides, thereby enhancing the material's wear resistance and toughness; in the heat treatment stage, the dissolution and precipitation of carbides can adjust the material's strength and toughness. This invention, on the one hand, adjusts the content of strong carbide-forming elements such as vanadium and titanium to form multiple carbides and control the morphology and quantity of carbides through a composite reinforced matrix; on the other hand, it controls carbon diffusion by adding non-carbide-forming elements such as silicon, thereby promoting carbide stabilization. The effect is good when the ratio of the two elements is 0.44≤(Ti+V+Zr+Nb) / (Si+Mg)≤1.27, which is beneficial to improving the material's weldability. Below this range, the amount of carbides is insufficient, making it difficult to obtain adequate wear resistance; above this range, the carbides tend to coarsen, reducing the material's toughness. In addition to forming carbides, carbon can also improve the matrix strength through interstitial solid solution, which is particularly important for materials with high chromium content. This invention preferably uses a carbon content of 0.32~0.45wt%, which improves the wear resistance of the material while achieving excellent strength and toughness.

[0042] Silicon (Si): Silicon is a low-cost element with significant effects. During quenching, silicon improves the hardenability of materials. During tempering, it accumulates around carbides, hindering carbon diffusion, thus adjusting carbide types and promoting their dispersed precipitation, improving tempering and thermal stability. At high temperatures, silicon adjusts the carbon aggregation sites, forming Cotillard atmospheres near dislocations, increasing high-temperature strength. Silicon is an important deoxidizing element, beneficial for reducing inclusion content and improving material strength. Silicon can also improve tempering resistance and enhance hardness and wear resistance through substitutional solid solution. Silicon's improvement on matrix hardness is more significant than that of tungsten and molybdenum, and it can partially replace higher-cost elements like tungsten and molybdenum, reducing costs while also improving fatigue strength to some extent. Adding silicon improves the material's resistance to oxidation and corrosion; however, excessive silicon can reduce plasticity. This invention preferably uses 0.47~0.65wt% silicon to achieve good hardness and wear resistance while improving thermal stability.

[0043] Mn: Manganese is an important solid solution strengthening element, significantly improving the strength and hardness of the matrix while having almost no impact on its plasticity and ductility, thus serving as a supplement to silicon-carbon solid solution strengthening. In this invention, the addition of silicon lowers the lower critical point during solidification or cooling, increases supercooling, improves the hardenability of the material, refines the microstructure, and improves overall mechanical properties. Manganese can adjust the secondary hardening temperature, promote the combination and precipitation of strong carbide-forming elements with carbon, increase the secondary hardening peak value, and improve the material's wear resistance. Manganese can also directly enter cementite in the form of substitutional atoms, forming alloy cementite and improving system stability. The combination of manganese and sulfur can reduce the formation of ferrous sulfide at grain boundaries, lowering the probability of material cracking. However, excessive manganese is detrimental to the high-temperature toughness of the material; this invention preferably uses 2.65~5.25 wt% manganese, achieving good plasticity while improving wear resistance.

[0044] Cr: Chromium is an important carbide-forming element, capable of forming various carbides. These carbides improve the hardness and thermal stability of materials and also serve as a chromium reserve, releasing chromium as a supplement when significant amounts evaporate or burn off. Chromium in chromium-containing carbides may be replaced by other elements at high temperatures, exhibiting a potential tendency to grow and coarsen. Therefore, it needs to be added in combination with titanium and nitrogen to form MC-type carbides with relatively higher thermal stability. These carbides are small in size and have high hardness, hindering carbide aggregation and growth while pinning dislocations to improve material toughness. Chromium significantly improves the oxidation and corrosion resistance of materials. The Cr₂O₃ it forms can isolate the oxidizing medium from further contact with the matrix, and its interaction with amorphous silicon-rich oxides and surface alumina can further enhance the oxidation resistance of materials. In corrosive environments, chromium can both shift the corrosion potential negatively and form chromium-dominant multi-component oxides, filling cracks and hindering further contact between the corrosive medium and the matrix. However, excessive chromium content can easily lead to a deterioration in the material's resistance to tempering. The present invention preferably uses 17.20~19.20 wt% chromium, which improves the material's resistance to oxidation and corrosion while achieving good thermal stability.

[0045] Vanadium (V) has a strong binding force with nitrogen, which can fix nitrogen in steel to form VN with high hardness and stability, improving the wear resistance of the material and blocking coarse chromium-containing carbides. Vanadium can also combine with carbon to form interstitial compounds represented by VC. VC has a hardness exceeding 2000 HV and a high melting point, which can improve the high-temperature strength and tempering stability of the material. The fine-sized and dispersed carbonitridion compounds of vanadium can pin grain boundaries, hinder grain coarsening, refine the matrix grains, and improve the toughness of the material, thereby correcting the disadvantage of easy coarsening of the microstructure caused by high chromium content. Vanadium can increase the self-diffusion activation energy of ferrite, and while replacing high-cost elements such as tungsten and molybdenum to improve the stability of the material, it also segregates near dislocations, hindering dislocation activation and slip, and improving the strength of the material. However, excessive vanadium will form a large amount of carbides, thereby reducing the solubility of carbon in the matrix and reducing its hardness. This invention preferably uses 0.23~0.47wt% vanadium to obtain good strength while improving the stability of the material.

[0046] Cobalt (Co) does not directly form carbides, but it can enhance the activity of carbon in the matrix by interacting with chromium and other elements, increasing the precipitation of alloy carbides during tempering and thus improving the secondary hardening effect. Furthermore, at high temperatures, cobalt inhibits the aggregation of carbide-forming elements such as chromium, thereby hindering carbide growth and improving the material's resistance to temper softening and high-temperature creep resistance. Moreover, when cobalt is dissolved in the matrix, it has a significant strengthening effect, effectively improving the material's structural stability and hardness. However, excessive cobalt increases cost and causes decarburization. This invention preferably uses 0.15~0.29 wt% cobalt to achieve excellent hardness and high-temperature creep resistance while improving the material's resistance to temper softening.

[0047] Ni (Ni): The combined action of nickel and chromium significantly improves the material's resistance to oxidation and corrosion in reducing media. In high-temperature oxidizing media, it can also form a composite oxide film, effectively hindering further contact between the medium and the matrix, thus improving the material's high-temperature oxidation resistance. Nickel dissolved in the matrix inhibits carbon diffusion by causing lattice distortion. Together with cobalt, which inhibits the diffusion of carbide-forming elements, it hinders carbide growth and coarsening, reducing stress concentration and preventing cracking. Furthermore, refined carbides can hinder grain boundary expansion, increasing the material's operating temperature range. Nickel effectively improves the material's hardenability, with a more significant effect when added together with chromium. Besides chromium, nickel can also interact with aluminum to form intermetallic compounds, inhibiting HAZ softening through secondary hardening and improving the material's hardness and strength. However, excessive nickel may reduce the material's thermal conductivity. This invention preferably uses 0.75~1.05wt% nickel to achieve good hardenability while improving the material's resistance to oxidation and corrosion.

[0048] Aluminum plays a multifaceted role in the technical solution of this invention. Firstly, while aluminum does not participate in carbide formation, it can weaken the bonding force between iron and carbon by adjusting the strength of metallic bonds in the matrix, influencing the microstructure transformation process and promoting the formation of harder carbides, thereby improving the material's red hardness. Secondly, aluminum is an important deoxidizing and nitrogen-fixing element, promoting the upward movement of oxygen and nitrogen in steel as inclusions, improving material purity. Furthermore, some aluminum-containing nitrides retained in the steel have a grain-refining effect, improving material toughness. When aluminum is added together with vanadium, the formation of single nitrides can be avoided, reducing the formation of coarse nitrides. Besides forming compounds, aluminum can also form intermetallic compounds, which are diffusely distributed and can effectively improve the material's high-temperature strength and wear resistance. Aluminum's improvement in strength and red hardness reduces the material's demand for cobalt and tungsten, contributing to cost reduction and efficiency improvement. Aluminum can significantly improve the material's resistance to oxidation and corrosion. In the matrix, it absorbs stress and reduces cracking in the form of highly ductile ferrite, or forms a passivation film on the surface, reducing the contact between oxidizing and corrosive media and the matrix. However, excessive aluminum content increases the difficulty of smelting the material. This invention preferably uses 0.14 to 0.23 wt% aluminum, which improves the hardness of the material while obtaining excellent resistance to oxidation and corrosion.

[0049] Ti: Titanium has a strong affinity for carbon and nitrogen elements, and the resulting compounds effectively inhibit grain growth during high-temperature holding. Titanium-containing compounds precipitated during forging or rolling can also hinder recrystallized grain growth, thus improving the material's strength and toughness. Titanium-containing nitrides, represented by TiN, exhibit better stability than vanadium-containing carbonitrides and precipitate earlier, thus compensating for the weakening of grain boundary bonding by vanadium-containing carbonitrides. Titanium-containing carbonitrides have higher hardness, improving the material's wear resistance. The addition of titanium modifies inclusions. Inclusions formed by the combination of titanium and sulfur are more spherical in shape than manganese-sulfur inclusions, improving the material's uniformity. The combination of titanium and oxygen reduces the number of aluminum spinel inclusions, forming composite inclusions and improving the material's machinability. However, excessive titanium may impair the material's fatigue performance. This invention preferably uses 0.05~0.10 wt% titanium to enhance the material's toughness while achieving good uniformity and machinability.

[0050] Nitrogen (N) is an important interstitial solid solution strengthening element, which can improve the hardness and wear resistance of the matrix. Nitrogen also simultaneously reduces the diffusion rate of carbon and chromium, delaying the growth of larger matrix particles (M). 23The formation and coarsening of C6 promotes the dispersed precipitation of carbides during tempering, improving both thermal stability and material hardness. Furthermore, nitrogen's entry into the interstitial spaces of the matrix lattice increases the resistance to dislocation activation or lattice slip, significantly enhancing the tensile strength of the material. Moreover, compared to carbon, it has less impact on the material's plasticity and toughness. Nitrogen can also react with alloying elements, especially when added together with chromium or vanadium, forming small amounts of dispersed Cr2N or VN. Their high hardness and good dispersion effectively complement the carbide precipitation strengthening. However, excessively high nitrogen content can affect the material's mirror finish and requires specific processing. This invention preferably uses a nitrogen content of 0.05~0.18 wt%, achieving good strength while improving wear resistance.

[0051] Mg: Magnesium plays multiple roles in this invention. First, because a nitrogen-enrichment process is required to increase nitrogen content, the vacuum level is reduced, which is detrimental to gas discharge and inclusion flotation. Therefore, magnesium and other elements are added to fix oxygen and sulfur elements and modify inclusions. Magnesium has a strong affinity for oxygen, which promotes the formation of MgO. MgO usually combines with Al2O3 to form a composite oxide, avoiding the formation of strip-shaped alumina inclusions and improving material strength. In addition, composite magnesium oxides can act as nucleation sites, refining grains and improving material toughness. Besides oxygen, magnesium also has a strong affinity for sulfur, and the magnesium inclusions formed are usually spindle-shaped or spherical, with smaller dimensions. Longer strip-shaped manganese inclusions are less harmful. Furthermore, magnesium inclusions have the function of absorbing phosphorus, existing on the outside of the magnesium inclusions in the form of phosphorus oxides, reducing the phosphorus content in the steel and improving material toughness. However, excessive magnesium is not conducive to improving the morphology of alloy carbides. The present invention preferably uses 0.002~0.007wt% magnesium to improve the strength of the material while obtaining good toughness.

[0052] Zr+Nb: Zirconium and niobium are both strong carbide-forming elements, preferentially forming MC-type carbides during solidification. These small carbides act as nucleation sites, increasing the nucleation rate and refining the grain size, thus improving material toughness. Furthermore, niobium can replace some vanadium atoms in VC, increasing the solid solubility of vanadium in the matrix and enhancing the degree of secondary hardening. In addition to forming carbides, zirconium's strong affinity for oxygen also contributes to its deoxidation function. During deoxidation, zirconium promotes the transformation of sulfide and silicate inclusions into fine oxide inclusions, and the sharp corners of the resulting composite inclusions are blunted into spherical shapes, improving material uniformity. Zirconium and niobium increase the material's coarsening temperature, reducing temper brittleness. However, excessive zirconium and niobium increase alloy costs. This invention preferably uses a total zirconium-niobium content of 0.01~0.03 wt%, achieving good uniformity while improving material hardness.

[0053] Ce: Cerium plays a multifaceted role in the technical solution of this invention. First, cerium is an important deoxidizing element. Its composite addition with aluminum, titanium, and other materials maximizes the removal of residual oxygen from molten steel, which is particularly beneficial for reducing vacuum operations during the smelting process to achieve higher nitrogen content. Second, the CeO formed during deoxidation acts as a nucleation core, promoting grain refinement and effectively mitigating the drawbacks of coarse columnar grains in the cast state, thus improving material toughness. Furthermore, cerium significantly increases the grain size of the weld heat-affected zone, enhancing the weldability of the material. Finally, the addition of cerium reduces the phosphorus and sulfur content at grain boundaries, effectively purifying them and reducing cracking during processing and use. However, excessive cerium content can easily generate brittle rare earth second phases, compromising material toughness. This invention preferably uses a cerium content of 0.005~0.010 wt%, achieving good purity and toughness while improving the material's weldability.

[0054] S and P: The harmful effects of sulfur and phosphorus elements in the technical solution of this invention outweigh their beneficial effects, and their content should be reduced as much as possible. However, from a scientific point of view, they cannot be completely removed, and from a practical and economic point of view, complete removal is unnecessary. Therefore, their content is reduced as much as possible through the composite addition of manganese, magnesium, zirconium, and rare earth elements, and the resulting inclusions are modified to reduce their adverse effects. Therefore, considering the desulfurization and phosphorus costs and their impact on performance, this invention controls the sulfur and phosphorus content to 0.015 wt% or below to obtain sufficient mechanical properties and achieve a cost balance.

[0055] The preparation method of the nitrogen-containing wear-resistant and oxidation-resistant mold steel of the present invention includes the following steps.

[0056] (1) Vacuum induction melting: After cleaning the furnace, the raw materials are sequentially filled into the vacuum induction melting process. The vacuum degree is less than 1 Pa for no less than 10 minutes. Nitrogen gas is injected into the furnace and manganese nitride is added. All of the materials are melted to obtain molten steel.

[0057] (2) Electrode ingot casting: Nitrogen gas is introduced, with a nitrogen partial pressure of 1.2~3.0 MPa. The molten steel obtained in step (1) is poured into a mold preheated to 290~300℃. After casting, it is slowly cooled to room temperature at a rate of 25~30℃ / h to obtain the electrode ingot.

[0058] (3) Electroslag remelting: After removing impurities from the electrode ingot obtained in step (2), it is placed in an ESR furnace and remelted under nitrogen protection using a slag system of MgO (4%~6%) and Ce2(CO3)3 (3%~5%). Manganese nitride is added and the ingot is cooled to obtain steel ingot.

[0059] (4) Rolling or forging: The steel ingot obtained in step (3) is rolled or forged.

[0060] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered at a quenching temperature of 1050~1085℃, cooled to room temperature and immediately tempered at a tempering temperature of 575~605℃ to obtain oxidation and corrosion resistant mold steel.

[0061] Further, in step (1), the packing sequence is as follows: iron, manganese, chromium, vanadium, and nickel are melted, followed by silicon, aluminum, cobalt, zirconium, and niobium, then manganese nitride is added, and finally the remaining raw materials are added. Electromagnetic induction and the skin effect are used to melt the raw materials layer by layer, ensuring thorough removal of inclusions and gases.

[0062] Furthermore, in step (1), the diameter of the manganese nitride raw material is less than 3.5 mm to avoid excessive melting time, which would affect production efficiency and cause loss of easily burnable elements.

[0063] Furthermore, in step (3), the dissolution rate of manganese nitride is 0.9~1.1wt% / min, and the manganese nitride particles are less than 2mm in diameter or are added in the form of manganese nitride powder wrapped in aluminum foil. This improves the melting efficiency.

[0064] Furthermore, in step (3), 1 / 7 to 2 / 7 of the baked return residue is added to reduce costs.

[0065] Furthermore, the cooling method in step (3) is pit cooling.

[0066] Furthermore, in step (4), when forging, a high-temperature diffusion treatment of 1190~1230℃ is performed before forging, the initial forging temperature is 1045~1155℃, the final forging temperature is 905~925℃, and the total forging ratio is 6.9~9.

[0067] Furthermore, step (4) adopts a combination of upsetting and drawing. When upsetting, the initial pressure is 30% for uniform upsetting, and then the pressure is increased. When drawing, cross forging is used to avoid coarse cracking of ferrite caused by high chromium.

[0068] Furthermore, the number of forgings in (4) is less than 4 times, and the time for each remelting is less than 40 minutes, to avoid coarse microstructure.

[0069] The principle of nitrogen-containing wear-resistant and oxidation-corrosion-resistant mold steel preparation method is as follows: the oxidation-corrosion resistance of the material is improved by using higher levels of chromium and other materials, the wear resistance is improved by adding nitrogen through a double melting method, and a small amount of rare earth elements and zirconium and niobium are added to improve the toughness of the material. The matching forming and heat treatment processes are also provided to finally prepare mold steel materials suitable for high-temperature oxidation and corrosion environments.

[0070] Beneficial effects: Compared with the prior art, the present invention has the following significant features.

[0071] 1. Oxidation and corrosion resistant high mirror finish large-size mold steel has good oxidation and corrosion resistance, good surface properties, improved mirror polishing performance, balanced comprehensive mechanical properties and is suitable for manufacturing large-size molds or parts, and is suitable for manufacturing glass or plastic parts with high precision and surface roughness requirements.

[0072] 2. Nitrogen-containing wear-resistant and oxidation-resistant mold steel: Nitrogen addition improves the wear resistance of the material, and rare earth elements improve the toughness of the material. It has good wear resistance and oxidation-resistant properties, relatively low cost and good comprehensive mechanical properties. It can be used in working conditions that are in direct contact with flames, such as waste-to-energy and has a wide range of applications. Detailed Implementation

[0073] The present invention will be further described below with reference to embodiments and comparative examples.

[0074] Example 1

[0075] The composition of the oxidation and corrosion resistant mold steel is detailed in Table 1 by weight percentage, where Zn / (Mg+La+Ce)=2.5 and B / (Zn+Ca)=0.096.

[0076] Table 1. Chemical composition of oxidation and corrosion resistant mold steel.

[0077] .

[0078] A method for preparing oxidation- and corrosion-resistant mold steel includes the following steps.

[0079] (1) Vacuum induction melting: The furnace lining of the vacuum induction furnace is prepared using CaO as the main material and MgO as the auxiliary material. Borax is added during the furnace opening process to ensure the stability of the furnace lining and to prevent the furnace lining from decomposing under low vacuum while improving the yield of calcium, magnesium and other minerals in the steel. Before melting, the furnace is washed with pure iron. Tungsten, molybdenum, nickel, manganese, chromium, copper and iron from the above raw materials are added into the furnace in sequence, with the metals with high melting points placed at the bottom. In the initial stage, the residual heat after furnace washing or low power is used to bake the raw materials to remove volatile impurities such as oil, sewage vapor and water vapor from the raw materials; vacuuming begins. When the vacuum degree is lower than 5 Pa, the power is increased to increase the vacuum degree, which promotes the skin effect on the surface of the raw materials and melts layer by layer from the outside to the inside. The impurities inside the raw materials are exposed to the vacuum and decompose and volatilize. The vacuum degree continues to decrease to 1 Pa, and the raw materials are completely melted. At this time, half of the aluminum and silicon are added to deoxidize and fix nitrogen while alloying. The power is increased and stirred for 10 min to promote the floating of inclusions and further removal of gases. After melting and clearing, argon gas is introduced. Under the protection of argon gas, volatile calcium, magnesium, and carbon are added. The carbon is wrapped in iron sheets, while the calcium and magnesium are added in the form of metal wires or wires. After melting, samples are taken to measure the composition. Based on the composition, the remaining aluminum, rare earth elements, boron, zinc, and other raw materials are added. The stirring power is increased. After the materials are added and melted, the steel is tapped and poured within 8 minutes. The tapping process is carried out under the protection of argon gas.

[0080] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0081] (3) Electroslag remelting: After removing impurities such as flash from the electrode ingot obtained in step (2), it is placed in an ESR furnace for electroslag remelting. A slag system of TiO2-Ce2O3-Al2O3 (4~10%) is used, which has a good effect on removing impurities and refining the structure, and has a good yield of magnesium, cerium and other materials. Remelting is carried out under argon protection to prevent oxygen, nitrogen and other materials from entering the slag liquid floating on the surface of the molten steel. The steel ingot is then cooled to obtain the steel ingot.

[0082] (4) Rolling or forging: The steel ingot obtained in step (3) is forged. Before forging, a high-temperature diffusion treatment is performed at 1260℃ for 30 hours. The initial forging temperature is 1135℃ and the final forging temperature is 955℃. Three upsetting and three drawing are adopted. When upsetting, a small reduction of 20% is used for uniform upsetting first, and then the reduction is increased to avoid material cracking. When drawing, cross forging is used to fully break down carbides and large matrix grains. After forging, the ingot is cooled with the furnace. The final total forging ratio is 7, which, together with the high-temperature diffusion process, improves the core segregation and promotes the refinement of columnar grains. The maximum corner crack size during the forging process is 34 mm × 30 mm × 4 mm.

[0083] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 500mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and it is held at 580℃ for 2h to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and uniform temperature for 1.5h. Finally, the heating rate is 100℃ / h to quenching temperature of 1060℃ and held for 13h. The maximum holding time is no more than 22h to avoid coarsening of the structure at high temperature. While ensuring the dissolution of carbides, the time is shortened as much as possible to save energy. The material is placed in an atomizing device with an air-water pressure ratio of 5:3. The pressure of the atomizing nozzle is 0.35MPa. The nozzle spray range covers the entire material and is evenly distributed in the radial direction to ensure the uniformity of the cooling rate. After cooling to room temperature, it is immediately tempered at a tempering temperature of 610℃ for 25h. It is tempered twice to promote secondary hardening and improve wear resistance, thus obtaining oxidation and corrosion resistant mold steel.

[0084] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface thickness of 0.020μm.

[0085] Example 2

[0086] The composition by weight percentage is shown in Table 1, where Zn / (Mg+La+Ce)=1 and B / (Zn+Ca)=0.139; the preparation of the oxidation and corrosion resistant mold steel includes the following steps.

[0087] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.8 Pa and held for 12 min to obtain molten steel.

[0088] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0089] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0090] (4) Forging: The steel ingot obtained in step (3) is forged. Before forging, it is subjected to high temperature diffusion treatment at 1245℃ for 28 hours. The initial forging temperature is 1150℃ and the final forging temperature is 960℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 8.

[0091] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 525mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2 hours to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5 hours. Finally, the temperature is raised to the quenching temperature of 1070℃ at a rate of 100℃ / h and held for 14 hours. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.40MPa. After cooling to room temperature, it is immediately tempered at a tempering temperature of 615℃ for 22 hours. The tempering is repeated twice to obtain oxidation and corrosion resistant mold steel.

[0092] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface thickness of 0.018μm.

[0093] Example 3

[0094] The composition by weight percentage is shown in Table 1, where Zn / (Mg+La+Ce)=1.5 and B / (Zn+Ca)=0.182; the preparation of the oxidation and corrosion resistant mold steel includes the following steps.

[0095] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.7 Pa and held for 12 min to obtain molten steel.

[0096] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0097] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0098] (4) Forging: The steel ingot obtained in step (3) is forged. Before forging, it is subjected to high temperature diffusion treatment at 1230℃ for 26 hours. The initial forging temperature is 1165℃ and the final forging temperature is 970℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 9.

[0099] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 550mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2 hours to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5 hours. Finally, the temperature is raised to the quenching temperature of 1080℃ at a rate of 100℃ / h and held for 15 hours. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.45MPa. After cooling to room temperature, it is immediately tempered at a tempering temperature of 620℃ for 23 hours. The tempering is repeated twice to obtain oxidation and corrosion resistant mold steel.

[0100] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface thickness of 0.018μm.

[0101] Example 4

[0102] The composition by weight percentage is shown in Table 1, where Zn / (Mg+La+Ce)=0.75 and B / (Zn+Ca)=0.242; the preparation of the oxidation and corrosion resistant mold steel includes the following steps.

[0103] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.5 Pa and held for 10 min to obtain molten steel.

[0104] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0105] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0106] (4) Forging: The steel ingot obtained in step (3) is forged. Before forging, it is subjected to high temperature diffusion treatment at 1220℃ for 24 hours. The initial forging temperature is 1180℃ and the final forging temperature is 980℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 7.

[0107] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 650mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2h to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5h. Finally, the temperature is raised at 100℃ / h to the quenching temperature of 1090℃ and held for 22h. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.50MPa. Since the material size is greater than 530mm, atomization cooling is adopted for 30s, air cooling for 10s, and tempering is carried out immediately after cooling to room temperature. The tempering temperature is 625℃ and the tempering time is 28h. The material is tempered twice to obtain oxidation and corrosion resistant mold steel.

[0108] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a diameter of 0.018 μm.

[0109] Example 5

[0110] The composition by weight percentage is shown in Table 1, where Zn / (Mg+La+Ce)=2 and B / (Zn+Ca)=0.227; the preparation of the oxidation and corrosion resistant mold steel includes the following steps.

[0111] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.5 Pa and held for 12 min to obtain molten steel.

[0112] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0113] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0114] (4) Forging: Before forging, a high-temperature diffusion treatment is carried out at 1210℃ for 22 hours. The initial forging temperature is 1185℃ and the final forging temperature is 970℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 8.

[0115] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 550mm. The material is heated in a furnace. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2h to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5h. Finally, the temperature is raised to the quenching temperature of 1100℃ at a rate of 100℃ / h and held for 15h. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.55MPa. Since the material size is greater than 530mm, atomization cooling is adopted for 30s, air cooling for 10s, and tempering is carried out immediately after cooling to room temperature. The tempering temperature is 630℃ and the tempering time is 24h. The material is tempered twice to obtain oxidation and corrosion resistant mold steel.

[0116] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface thickness of 0.020μm.

[0117] Example 6

[0118] The composition by weight percentage is shown in Table 1, where Zn / (Mg+La+Ce)=1.25 and B / (Zn+Ca)=0.182; the preparation of the oxidation and corrosion resistant mold steel includes the following steps.

[0119] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.9 Pa and held for 14 min to obtain molten steel.

[0120] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0121] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0122] (4) Forging: Before forging, a high-temperature diffusion treatment is carried out at 1200℃ for 20 hours. The initial forging temperature is 1190℃ and the final forging temperature is 960℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 9.

[0123] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 650mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2h to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5h. Finally, the temperature is raised at 100℃ / h to the quenching temperature of 1100℃ and held for 17h. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.55MPa. Since the material size is greater than 530mm, atomization cooling is adopted for 30s, air cooling for 10s, tempering temperature is 645℃, tempering time is 30h, and tempering is performed twice to obtain oxidation and corrosion resistant mold steel.

[0124] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after wire cutting is polished. First, it is rough polished with a grinding wheel, and then polished step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with 0.019μm.

[0125] Application Example 1

[0126] The oxidation- and corrosion-resistant mold steel prepared using the method described in this invention is used to manufacture molds for composite fiber-reinforced hulls on small boats or rowboats, with dimensions not less than 3m × 2m × 0.1m. The prepared molds exhibit good dimensional stability under over 1000 cycles of thermal cycling, with deformation ≤0.1 mm / m. Furthermore, it demonstrates corrosion resistance comparable to 304 stainless steel in the volatiles released during resin curing. Molds prepared using the material formulation and process of this invention have high mirror finish, resulting in smooth surface on the rowboat hull, low water resistance, and reduced physical or energy consumption.

[0127] Comparative Example 1

[0128] Unlike Example 1, Comparative Example 1 includes the components shown in Table 1 by weight percentage, wherein Zn / (Mg+La+Ce)=0.2 and B / (Zn+Ca)=0.25; the prepared oxidation-resistant and corrosion-resistant mold steel includes the following steps.

[0129] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 1.2 Pa and held for 6 min to obtain molten steel.

[0130] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0131] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0132] (4) Forging: The steel ingot obtained in step (3) is forged. Before forging, it is subjected to high temperature diffusion treatment at 1200℃ for 28 hours. The initial forging temperature is 1125℃ and the final forging temperature is 950℃. Three upsetting and three drawing are adopted. The final total forging ratio is 6. The average corner crack size of the forging is 55 mm × 36 mm × 5 mm.

[0133] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 550mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2 hours to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5 hours. Finally, the temperature is raised at 100℃ / h to the quenching temperature of 1050℃ and held for 15 hours. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.65MPa. Since the material size is greater than 530mm, atomization cooling is adopted for 30 seconds, air cooling for 10 seconds, tempering temperature is 600℃, tempering time is 30 hours, and tempering is performed twice to obtain oxidation and corrosion resistant mold steel.

[0134] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface thickness of 0.020μm.

[0135] Comparative Example 2

[0136] Unlike Example 1, Comparative Example 2 includes the components shown in Table 1 by weight percentage, wherein Zn / (Mg+La+Ce)=0.5 and B / (Zn+Ca)=0; the prepared oxidation-resistant and corrosion-resistant mold steel includes the following steps.

[0137] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.9 Pa and held for 8 min to obtain molten steel.

[0138] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0139] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0140] (4) Forging: The steel ingot obtained in step (3) is forged. Before forging, it is subjected to high temperature diffusion treatment at 1200℃ for 26 hours. The initial forging temperature is 1150℃ and the final forging temperature is 945℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 8.

[0141] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 600mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and it is held at 580℃ for 2 hours to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and uniform temperature for 1.5 hours. Finally, the heating rate is 100℃ / h to quenching temperature of 1075℃ and held for 20 hours. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.65MPa. Since the material size is greater than 530mm, atomization cooling for 30s and air cooling for 10s are adopted to cool to room temperature. Then, it is immediately tempered. The tempering temperature is 660℃ and the tempering time is 24 hours. The tempering is performed twice to obtain oxidation and corrosion resistant mold steel.

[0142] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a thickness of 0.025μm.

[0143] Comparative Example 3

[0144] Unlike Example 1, Comparative Example 3 includes the composition shown in Table 1 by weight percentage, wherein Zn / (Mg+La+Ce)=0 and B / (Zn+Ca)=3.75; the prepared oxidation-resistant and corrosion-resistant mold steel includes the following steps.

[0145] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.8 Pa and held for 10 min to obtain molten steel.

[0146] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. After casting, the molten steel is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0147] (3) Electroslag remelting: Electroslag remelting and cooling to obtain steel ingots.

[0148] (4) Forging: Before forging, a high-temperature diffusion treatment is carried out at 1180℃ for 24 hours. The initial forging temperature is 1175℃ and the final forging temperature is 960℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 9.

[0149] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 650mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2h to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5h. Finally, the temperature is raised at 100℃ / h to the quenching temperature of 1100℃ and held for 22h. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.30MPa. Since the material size is greater than 530mm, atomization cooling is adopted for 30s, air cooling for 10s, and tempering is carried out immediately after cooling to room temperature. The tempering temperature is 640℃ and the tempering time is 24h. The material is tempered twice to obtain oxidation and corrosion resistant mold steel.

[0150] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface thickness of 0.024μm.

[0151] Comparative Example 4

[0152] Unlike Example 1, Comparative Example 4 includes the components shown in Table 1 by weight percentage, wherein Zn / (Mg+La+Ce)=2.67 and B / (Zn+Ca)=0.1875; the prepared oxidation-resistant and corrosion-resistant mold steel includes the following steps.

[0153] (1) Vacuum induction melting: The vacuum degree is continuously reduced to 0.8 Pa and held for 10 min to obtain molten steel.

[0154] (2) Electrode ingot casting: The molten steel obtained in step (1) is cast into a mold preheated to 300°C. During the casting process, care should be taken to avoid bringing impurities from the surface of the molten steel into the mold. The casting temperature is 350°C and the ingot is sent to a slow cooling pit. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0155] (3) Electroslag remelting: Electroslag remelting uses a slag system of 4~10% Al2O3. After electroslag remelting and cooling, steel ingots are obtained.

[0156] (4) Forging: Before forging, a high-temperature diffusion treatment is carried out at 1180℃ for 24 hours. The initial forging temperature is 1175℃ and the final forging temperature is 960℃. Three upsetting and three drawing are adopted, and the final total forging ratio is 9.

[0157] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered. The material size is 650mm. The material is loaded into the furnace and heated. The first stage heating rate is 65℃ / h, and the temperature is held at 580℃ for 2h to reduce stress. The second stage heating rate is 85℃ / h to 870℃ and the temperature is uniform for 1.5h. Finally, the temperature is raised at 100℃ / h to the quenching temperature of 1100℃ and held for 22h. The material is placed in an atomizing device with an air-water pressure ratio of 5:3 and an atomizing nozzle pressure of 0.30MPa. Since the material size is greater than 530mm, atomization cooling is adopted for 30s, air cooling for 10s, and tempering is carried out immediately after cooling to room temperature. The tempering temperature is 640℃ and the tempering time is 24h. The material is tempered twice to obtain oxidation and corrosion resistant mold steel.

[0158] (6) Surface treatment: The obtained oxidation and corrosion resistant mold steel is subjected to surface treatment. The material after milling and wire cutting is polished. First, rough polishing is performed with a grinding wheel, and then polishing is performed step by step with 100~1200# sandpaper. Then, the material is degreased and polished with polishing cloth and polishing paste for final fine polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a thickness of 0.024μm.

[0159] Material performance testing.

[0160] The materials prepared in Examples 1-6 and Comparative Examples 1-4 were processed into cylindrical samples with a diameter of 10 mm and a length of 5 mm, and connected to copper wires. Except for the working surface, the remaining parts of the samples were isolated from the corrosive liquid. After polishing the sample surface, it was etched with a 3.5% NaCl aqueous solution. The dynamic polarization curves were tested in an electrochemical workstation to obtain the self-corrosion potential (V) and self-corrosion current (A / cm). 2 Hardness testing was conducted according to the national standard GB / T 230.1-2018, including hardness at different locations from the edge of the material cross-section to the core. High-temperature oxidation resistance testing at 1000 ℃ was conducted according to the national standard GB / T 13303-1991. The surface roughness, average hardness value, maximum hardness difference at different locations, and oxidation weight gain data are detailed in Table 2.

[0161] Table 2. Material performance test parameters obtained from Examples 1-6 and Comparative Examples 1-4.

[0162]

[0163] In summary, the oxidation and corrosion resistant mold steel of this invention strengthens the material through the complementary effects of its components, improves mirror polishing performance by replacing some carbides with intermetallic compounds, enhances oxidation and corrosion resistance with higher levels of chromium and aluminum, and, combined with smelting, forming, and heat treatment processes, produces large-scale materials with high uniformity, suitable for manufacturing glass, rubber, plastics, and other comprehensive working conditions such as high-temperature oxidation and corrosion.

[0164] The following are examples and comparative examples of the nitrogen-containing wear-resistant and oxidation-resistant mold steel described in this invention.

[0165] Example 7

[0166] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.475.

[0167] Table 3 Chemical composition of nitrogen-containing wear-resistant and oxidation-resistant mold steel.

[0168]

[0169] Nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following steps.

[0170] (1) Vacuum induction melting: Before melting, the furnace is cleaned with the same material or pure iron to remove potential impurity elements. Iron, manganese, chromium, vanadium, and nickel fillers are added to the vacuum induction melting process, with high-melting-point raw materials placed at the bottom and pure iron placed at the top. The raw materials are baked using residual heat from the furnace cleaning or low power to remove volatile impurities adhering to the surface of the raw materials. Vacuuming is started and power is supplied. The raw materials are melted layer by layer from the outside to the inside using electromagnetic induction and skin effect, which fully degassing and promotes the floating of inclusions. When the vacuum degree drops to 5 Pa, the power is gradually increased. After the raw materials are melted, vacuuming continues, and the vacuum degree is kept below 1 Pa for 10 min. Stirring promotes the floating or discharge of inclusions and gases. Then, alloying elements such as silicon, aluminum, cobalt, zirconium, and niobium are added and stirred for 5 min to discharge gases and combine and modify the remaining gaseous elements and impurities such as sulfur and phosphorus. After melting is complete, nitrogen is injected into the furnace until the nitrogen pressure inside the furnace reaches 1.1 MPa. Then, manganese nitride with an average particle size of 3.5 mm is added to increase the nitrogen content. Manganese nitride has a lower melting point than chromium nitride, and the use of small particle size is conducive to rapid melting, so as to avoid the loss of elements such as magnesium due to excessive melting time.

[0171] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 1.2 MPa. The higher pressure helps to improve the quality of the riser position, which can reduce the amount of sawing at the head of the electrode ingot after casting and improve the yield. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0172] (3) Electroslag remelting: After removing the flash and grinding the surface of the electrode ingot obtained in step (2), it is baked to remove impurities such as water vapor and then electroslag remelted in an ESR furnace using Al2O3 4~6%. 、 Pre-melted slag with 33-5% Ce2(CO3) is electroslag remelted, and a quarter of the return slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830℃ for 3.5 hours to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. Cutting chips of the same material are cleaned, dried, and placed in the center of the bottom pad. The slag mixed with manganese nitride is placed on the periphery, and the furnace is loaded with nitrogen gas at 0.5 MPa to initiate arc slagging. A high current is used in the initial stage. When 2 / 3 of the slag has melted, the nitrogen gas charge is increased until the pressure reaches 1.1 MPa. After the slag melts, manganese nitride wrapped in aluminum foil is added at a melting rate of 0.9 wt% / min. After the slagging stage is completed, manganese nitride is added at a melting rate of 1.1 wt% / min. During the feeding stage, manganese nitride is added until the melting is completed. During electroslag remelting, the nitrogen pressure, slightly higher than atmospheric pressure, provides good nitrogen retention, nitrogen enrichment, and oxygen removal while placing lower demands on equipment performance. Powdered manganese nitride is beneficial for raw material melting and nitrogen enrichment. After electroslag remelting, the crystallizer continues to be cooled by water for 1 hour before demolding and being sent to a slow cooling pit or stress-relief annealing process to prevent cracking.

[0173] (4) Forging: The steel ingot obtained in step (3) is forged; a high-temperature diffusion treatment at 1190℃ is performed before forging, the initial forging temperature is 1045℃, and the final forging temperature is 925℃. Upsetting and drawing are combined, with three upsettings and three drawings, and the reheating time is less than 40 min each time to avoid coarse microstructure. During the forging process, when forging or upsetting for the first time, the reduction is less than 30% and the upsetting is uniform to avoid coarse cracking of ferrite caused by high chromium. The reduction is then increased, and cross-forging is used when drawing to avoid coarse cracking of ferrite caused by high chromium. The final forging ratio is 7.0, and the number of forgings is 4.

[0174] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered at a quenching temperature of 1050℃. After cooling to room temperature, it is immediately tempered at a tempering temperature of 605℃ to obtain oxidation and corrosion resistant mold steel. The selection of quenching and tempering temperatures is related to the composition in order to give full play to the hardening effect of elements such as manganese, nickel and zirconium.

[0175] Example 8

[0176] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.713. Its preparation method includes the following steps.

[0177] (1) Vacuum induction melting: After melting is complete, nitrogen is injected into the furnace until the nitrogen pressure in the furnace reaches 1.5 MPa, and manganese nitride is added to increase nitrogen, and molten steel is obtained.

[0178] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 1.2 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0179] (3) Electroslag remelting: Using pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5%, electroslag remelting is performed. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.2MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process.

[0180] (4) Forging and forming: Before forging, a high-temperature diffusion treatment at 1190℃ is performed, with an initial forging temperature of 1060℃ and a final forging temperature of 925℃. An upsetting and drawing method is adopted, with three upsettings and three drawings, and each reheating time is less than 40 minutes. During the first upsetting, the reduction is less than 30% for uniform upsetting, and then the reduction is increased. Cross forging is used during drawing. The final forging ratio is 6.9, and the number of forgings is 3.

[0181] (5) Heat treatment: Quenching temperature 1055℃, cooling to room temperature and immediately tempering at 600℃ to obtain oxidation and corrosion resistant mold steel.

[0182] Example 9

[0183] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.993. Its preparation method includes the following steps.

[0184] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 2.0 MPa to obtain molten steel.

[0185] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 2.5 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0186] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830 ℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.1MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0187] (4) Forging and forming: Before forging, a high-temperature diffusion treatment at 1200℃ is performed, with an initial forging temperature of 1080℃ and a final forging temperature of 925℃. An upsetting and drawing method is adopted, with each reheating time less than 40 min. During the forging process, during the initial upsetting, the reduction is less than 30% for uniform upsetting, and then the reduction is increased. Cross-forging is used during drawing. The final forging ratio is 8.2, and the number of forgings is 3.

[0188] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered at a quenching temperature of 1060℃ and immediately tempered at a tempering temperature of 595℃ after cooling to room temperature to obtain oxidation and corrosion resistant mold steel.

[0189] Example 10

[0190] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.713. Its preparation method includes the following steps.

[0191] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 2.5 MPa to obtain molten steel.

[0192] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 2.5 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0193] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830 ℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.5MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0194] (4) Forging and forming: Before forging, a high-temperature diffusion treatment at 1220℃ is performed, with an initial forging temperature of 1100℃ and a final forging temperature of 925℃. An upsetting and drawing method is adopted, with each reheating time less than 40 minutes to avoid coarse microstructure. During the forging process, during the initial upsetting, the reduction is less than 30% for uniform upsetting, and then the reduction is increased. Cross-forging is used during drawing. The final forging ratio is 8.0, and the number of forgings is 3.

[0195] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered at a quenching temperature of 1065℃ and immediately tempered at a tempering temperature of 590℃ after cooling to room temperature to obtain oxidation and corrosion resistant mold steel.

[0196] Example 11

[0197] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.966. Its preparation method includes the following steps.

[0198] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 3.0 MPa to obtain molten steel.

[0199] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 3.0 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0200] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.1MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0201] (4) Forging and forming: Before forging, a high-temperature diffusion treatment at 1230℃ is performed, with an initial forging temperature of 1125℃ and a final forging temperature of 925℃. An upsetting and drawing method is adopted, with each reheating time less than 40 minutes to avoid coarse microstructure. During the forging process, during the initial upsetting, the reduction is less than 30% for uniform upsetting, and then the reduction is increased. Cross-forging is used during drawing. The final forging ratio is 9.0, and the number of forgings is 3.

[0202] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered at a quenching temperature of 1075℃ and immediately tempered at a tempering temperature of 585℃ after cooling to room temperature to obtain oxidation and corrosion resistant mold steel.

[0203] Example 12

[0204] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=1.174. Its preparation method includes the following steps.

[0205] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 4.3 MPa to obtain molten steel.

[0206] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 3.0 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0207] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.5MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0208] (4) Forging: The steel ingot obtained in step (3) is forged; a high-temperature diffusion treatment at 1230℃ is performed before forging, the initial forging temperature is 1155℃, and the final forging temperature is 925℃. Upsetting and drawing are combined, and the reheating time is less than 40 min each time to avoid coarse structure. During the forging process, the initial upsetting is less than 30% uniform upsetting, and then the downsetting is increased. Cross forging is used during drawing. The final forging ratio is 9.0, and the number of forgings is 3.

[0209] (5) Heat treatment: Quenching temperature 1085℃, cooling to room temperature and immediately tempering at 575℃ to obtain oxidation and corrosion resistant mold steel.

[0210] Comparative Example 5

[0211] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.239. Its preparation method includes the following steps.

[0212] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 2.0 MPa to obtain molten steel.

[0213] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 0.9 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0214] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830 ℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 0.5MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0215] (4) Forging: The steel ingot obtained in step (3) is forged; a high-temperature diffusion treatment at 1250℃ is performed before forging, with an initial forging temperature of 1030℃ and a final forging temperature of 925℃. An upsetting and drawing method is adopted, with each reheating time less than 40 min to avoid coarse microstructure. During the forging process, the initial upsetting is less than 30% uniform upsetting, and the downsetting is increased thereafter. Cross-forging is used during drawing. The final forging ratio is 9.0, and the number of forgings is 3.

[0216] (5) Heat treatment: Quenching temperature 1090℃, cooling to room temperature and then immediately tempering at 615℃ to obtain oxidation and corrosion resistant mold steel.

[0217] Comparative Example 6

[0218] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=1.337. Its preparation method includes the following steps.

[0219] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 2.9 MPa to obtain molten steel.

[0220] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 2.0 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0221] (3) Electroslag remelting: Using pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5%, electroslag remelting is performed. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.0MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0222] (4) Forging: The steel ingot obtained in step (3) is forged; a high-temperature diffusion treatment at 1230℃ is performed before forging, the initial forging temperature is 1070℃, and the final forging temperature is 925℃. Upsetting and drawing are combined, and the reheating time is less than 40 min each time to avoid coarse structure. During the forging process, the initial upsetting is less than 30% uniform upsetting, and then the downsetting is increased. Cross forging is used during drawing. The final forging ratio is 8.0, and the number of forgings is 3.

[0223] (5) Heat treatment: The steel ingot obtained in step (4) is quenched and tempered at a quenching temperature of 1060℃ and immediately tempered at a tempering temperature of 580℃ after cooling to room temperature to obtain oxidation and corrosion resistant mold steel.

[0224] Comparative Example 7

[0225] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=0.098. Its preparation method includes the following steps.

[0226] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 4.0 MPa to obtain molten steel.

[0227] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 3.0 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0228] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. One-quarter of the returned slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830 ℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 1.5MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After the electroslag remelting is completed, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0229] (4) Forging: The steel ingot obtained in step (3) is forged; a high-temperature diffusion treatment at 1210℃ is performed before forging, the initial forging temperature is 1120℃, and the final forging temperature is 925℃. Upsetting and drawing are combined, and the reheating time is less than 40 min each time to avoid coarse structure. During the forging process, the initial upsetting is less than 30% uniform upsetting, and then the downsetting is increased. Cross forging is used during drawing. The final forging ratio is 8.1, and the number of forgings is 3.

[0230] (5) Heat treatment: Quenching temperature 1030℃, cooling to room temperature and immediately tempering at 615℃ to obtain oxidation and corrosion resistant mold steel.

[0231] Comparative Example 8

[0232] The nitrogen-containing wear-resistant and oxidation-resistant mold steel includes the following composition by weight percentage, as detailed in Table 3, where (Ti+V+Zr+Nb) / (Si+Mg)=1.629. Its preparation method includes the following steps.

[0233] (1) Vacuum induction melting: After melting is complete, nitrogen gas is injected into the furnace until the nitrogen pressure in the furnace reaches 5.2 MPa to obtain molten steel.

[0234] (2) Electrode ingot casting: After baking the casting mold, place it in the casting chamber and fill it with nitrogen gas. The nitrogen partial pressure is 3.0 MPa. The molten steel obtained in step (1) is poured into the mold preheated to 300°C. The casting temperature is 350°C. After casting, it is slowly cooled to room temperature at a rate of 30°C / h to obtain the electrode ingot.

[0235] (3) Electroslag remelting: Pre-melted slag with Al2O3 4~6% and Ce2(CO3)3 3~5% is used for electroslag remelting. 1 / 4 of the recycled slag with a particle size of less than 8mm is added to reduce costs. Before use, the slag is baked at 830 ℃ for 3.5h to degas and reduce hydrogen content. 0.12% of the ingot weight of manganese nitride particles with a diameter of less than 2mm is added for nitrogen enrichment. After the pressure reaches 2.0MPa and the slag melts, manganese nitride wrapped in aluminum foil is added. After electroslag remelting, the crystallizer continues to be cooled by water for 1h, and then demolded and sent to a slow cooling pit or stress-relief annealing process to avoid cracking.

[0236] (4) Forging and forming: Before forging, a high-temperature diffusion treatment at 1180℃ is performed, with an initial forging temperature of 1170℃ and a final forging temperature of 925℃. An upsetting and drawing method is adopted, with each reheating time less than 40 min to avoid coarse microstructure. During the forging process, during the initial upsetting, the reduction is less than 30% for uniform upsetting, and then the reduction is increased. Cross-forging is used during drawing. The final forging ratio is 7.0, and the number of forgings is 3.

[0237] (5) Heat treatment: Quenching temperature 1010℃, cooling to room temperature and immediately tempering at 580℃ to obtain oxidation and corrosion resistant mold steel.

[0238] Material performance testing.

[0239] Material properties of the nitrogen-containing oxidation-resistant mold steels obtained in Examples 7-12 and Comparative Examples 5-8 were tested. Oxidation weight gain was tested at 1000 °C for 100 h under atmospheric conditions. The materials were then immersed in molten aluminum at 750 °C for 2 h to test their resistance to aluminum molten aluminum corrosion. No large-area or multi-point peeling was observed on the surface. The measured data for material hardness, oxidation weight gain, and weight loss rate are detailed in Table 4.

[0240] Table 4. Material performance test data obtained from Examples 7-12 and Comparative Examples 5-8.

[0241]

[0242] Application examples

[0243] The material prepared by the method described in this invention exhibits excellent comprehensive properties. Taking Example 12 as an example, through the synergy between components and a manufacturing process matching the components, fewer cracks occur during manufacturing, and the yield is 5.3% higher than that of Comparative Examples 5-8. Furthermore, the final product exhibits balanced hardness, oxidation resistance, and corrosion resistance. The metal powder die-casting mold prepared from the material of Example 12, without the need for surface strengthening treatment, can withstand over 5000 applications at temperatures above 800°C, representing a 15% improvement over conventional materials and comparative examples.

[0244] In summary, the nitrogen-containing wear-resistant and oxidation-resistant mold steel material described in this invention has high hardness and excellent resistance to oxidation and corrosion. It is well-suited for molding plastics, glass, or metallic aluminum and titanium, and has broad application prospects in environments where it comes into direct contact with flames or high-temperature oxidizing atmospheres.

Claims

1. A mold steel resistant to oxidation and corrosion, characterized in that, The composition includes the following components by weight percentage: C: 0.36~0.47%, Si: 0.81~0.89%, Mn: 0.83~1.21%, Cr: 19.41~22.51%, Mo: 0.07~0.10%, W: 0.02~0.03%, Al: 4.75~5.25%, Ni: 0.50~0.75%, Cu: 0.01~0.02%, Mg: 0.01~ 0.02%, Zn: 0.03~0.05%, Ca: 0.002~0.005%, B: 0.005~0.010%, La and Ce: 0.01~0.02%, S≤0.011%, P≤0.020%, with the balance being Fe and unavoidable trace impurities, and satisfying 0.75≤Zn / (Mg+La+Ce)≤2.50, 0.09≤B / (Zn+Ca)≤0.

31.

2. The oxidation- and corrosion-resistant mold steel according to claim 1, characterized in that, The total content of O and N in the trace impurities is: O+N≤12 ppm.

3. The oxidation- and corrosion-resistant mold steel according to claim 1, characterized in that, The mass percentage of P is P≤0.005wt%.

4. A method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 1, characterized in that, Includes the following steps: (1) Vacuum induction melting: The raw materials are sequentially filled into the vacuum induction melting process. The vacuum degree is less than 1 Pa for a period of not less than 10 min. The melting is carried out under argon protection to obtain molten steel. (2) Electrode ingot casting: The molten steel obtained in step (1) is poured into a mold preheated to 280~300℃. After casting, it is slowly cooled to room temperature at a rate of 25~35℃ / h to obtain an electrode ingot. (3) Electroslag remelting: After removing impurities from the electrode ingot obtained in step (2), it is placed in an ESR furnace and electroslag remelted using a TiO2-Ce2O3-Al2O3 slag system under argon protection. The ingot is then cooled to obtain a steel ingot. (4) Rolling or forging: The steel ingot obtained in step (3) is rolled or forged; (5) Heat treatment: Quenching and tempering the steel ingot obtained in step (4) at a quenching temperature of 1060~1110℃, cooling to room temperature and then immediately tempering at a tempering temperature of 610~645℃ to obtain oxidation and corrosion resistant mold steel.

5. The method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 4, characterized in that, This includes surface processing of the oxidation and corrosion resistant mold steel obtained in step (5), followed by fine grinding and polishing to obtain a high mirror finish oxidation and corrosion resistant mold steel with a surface roughness of less than 0.020 μm.

6. The method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 4, characterized in that, In step (1), the filler sequence is tungsten, molybdenum, nickel, manganese, chromium, copper, and iron. After melting, 1 / 2 to 2 / 3 of aluminum and silicon are added. When the vacuum degree is less than 1 Pa, calcium, magnesium, and carbon are added. Finally, the remaining raw materials are added.

7. The method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 4, characterized in that, When forging in step (4), a high-temperature diffusion treatment of 1200~1260℃ is performed before forging, the initial forging temperature is 1135~1190℃, the final forging temperature is 955~980℃, and the total forging ratio is 7~9. The upsetting and drawing method is adopted. When upsetting, the small reduction amount of 20% is used for uniform upsetting first, and then the reduction amount is increased. When drawing, cross forging is adopted.

8. The method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 4, characterized in that, The quenching holding time in step (5) is 1.1~1.6 min / mm, and the tempering holding time is 2.5~3 min / mm.

9. The method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 4, characterized in that, The quenching temperature conditions for step (5) are as follows: the first stage heating rate is 60~65℃ / h to 560~580℃ and the temperature is held for 1.5~2 h; the second stage heating rate is 80~85℃ / h to 850~870℃ and the temperature is uniform for 1.5~2 h; and finally the temperature is raised to the quenching temperature at a rate of 95~100℃ / h.

10. The method for preparing oxidation-resistant and corrosion-resistant mold steel according to claim 4, characterized in that, In step (5), the cooling adopts a combination of atomization cooling and air cooling, with an air-water pressure ratio of 5:2.5~3.5 and an atomization nozzle pressure of 0.35~0.55MPa.

Citation Information

Patent Citations

  • A preparation process for corrosion-resistant mold steel

    CN103060698B

  • Hardening and tempering method of novel anti-corrosion glass die steel large-section forging material

    CN105483334A

  • Prostate cancer full nutrient food, and preparation method thereof

    CN108902933A

  • Corrosion-resistant mirror surface die steel and manufacturing method thereof

    CN113061801A

  • High-hardness and high-toughness rust-proof die steel and production process thereof

    CN113584380A

Cited By

  • Large-size high-carbon die steel containing rare earth elements and preparation method thereof

    CN121737588A